(untitled) (Communications in Mathematical Research, 2019)
This paper is concerned with the asymptotic behavior of the solution u_ε of a p-Ginzburg-Landau system with the radial initial-boundary data. The author proves that the zeros of u_ε in the parabolic domain B_1(0)× (0, T] locate near the axial line {0}×(0, T]. In particular, all the zeros converge to this axial line when the parameter ε goes to zero.